Pola Asuh Keluarga Dalam Pembentukan Norma Sosial Mahasiswa Sosiologi UIN Sunan Gunung Djati Bandung - Rifaldi Azhar Suhendi; Muhammad Naufal Assidhiqi; Fahmi Muhammad Hanif; Sri Dayamanti (Universitas Negeri Medan, 2026)
The weakening internalization of social values ​​and norms among university students demonstrates the crucial role of the family as the primary environment in character formation. The family plays a key role as a primary socialization agent, shaping an individual's attitudes, behavior, and ability to interact in the social environment. This study aims to analyze the role of family parenting styles in the formation of social norms among Sociology students, Class of 2023, at UIN Sunan Gunung Djati Bandung. The study used a descriptive qualitative approach with purposive sampling. Data were obtained through in-depth interviews, observation, and documentation. The results indicate that democratic parenting styles tend to produce students with discipline, responsibility, good communication skills, and greater adaptability to social environments. Meanwhile, permissive parenting styles tend to lead to less controlled behavior and a weak awareness of social norms. The findings of this study demonstrate that family parenting styles have a significant influence on the formation of students' social norms and the development of social character in campus life.